Implementation of Religious Moderation in Muslim Families Bagan Siapiapi, Riau in the Perspective of Fath al-Dzarī’ah - Arisman, Arisman; Harmanto, Adi; Sobirin, Imam (al-'adalah, 2023)
This article aims to describe the concrete efforts made by Muslim families in Bagansiapiapi, Riau in implementing the concept of religious moderation to create a harmonious atmosphere in the midst of a pluralistic society. This research is a field research, with a sociological-empirical approach. Data collection techniques are carried out by observation, interviews and documentation. The research informants consist of ten Muslim families in Bagan Siapiapi as key informants. The data that have been collected are then processed to be analyzed qualitatively-descriptively-analystically through the fath al-dzarī’ah theory. The results of this study indicate that there are four efforts of religious moderation that have been implemented by the Bagan Siapiapi community, namely: first, the "Clean City" activity. Second, the "Bakar Tongkak" activity. Third, regular meetings of the Interfaith Harmony Forum (FKUB). Fourth, prevention of intra and interfaith conflicts in society. The activities of “Cleaning the City”, “Bakar Tongkak”, and the regular meetings of the Interfaith Harmony Forum, from the perspective of fath al-dzarī’ah, are forms of al-dzarī’ah or means to create religious moderation whose ultimate goal is for the good or welfare of the heterogeneous Bagan Siapiapi community. As achieving welfare is highly recommended in Islam, all activities that lead to the common good must continue to be encouraged (fath).